Prototypes are Key Heuristic Information in Insight Problem Solving. Issue 1 (2nd January 2016) - Yang, Wenjing; Dietrich, Arne; Liu, Peiduo; Ming, Dan; Jin, Yule; Nusbaum, Howard C.; Qiu, Jiang; Zhang, Qinglin
Abstract : Evidence from a range of fields indicates that inventions are often inspired by drawing a parallel to solutions found in nature. However, the cognitive mechanism of this process is not well understood. The cognitive mechanism of heuristic prototype in scientific innovation was tested with 3 experiments. First, 84 historical accounts of important scientific innovations were collected and the prototype solution underlying them was extracted. Experiment 1 tested the validity of these materials and showed that knowledge of the prototype facilitated insight solutions. Experiment 2 and 3 suggested that activation of the prototype was indeed the critical element in the process of insight. Also, the mechanism of this activation was linked to the semantic similarity between the feature function of the prototype and the required function of the problem. In addition, Experiment 3 showed that participants who were better at excluding interference information more readily activated the relevant prototype. To sum up, the experiments suggested that activating a memory of the heuristic prototype was important in solving scientific innovation insight problems. Activating the feature function of right heuristic prototype and linking it by way of semantic similarity to the required function of the problem was the key mechanism people used to solve scientific insight problem.